Extra‐hepatic manifestations of autochthonous hepatitis E infection. Issue 11 (10th October 2014) - Woolson, K. L.; Forbes, A.; Vine, L.; Beynon, L.; McElhinney, L.; Panayi, V.; Hunter, J. G.; Madden, R. G.; Glasgow, T.; Kotecha, A.; Dalton, H. C.; Mihailescu, L.; et al.
Summary Background Autochthonous (locally acquired) hepatitis E is increasingly recognised in developed countries, and is thought to be a porcine zoonosis. A range of extra‐hepatic manifestations of hepatitis E infection have been described, but have never been systematically studied. Aim To report the extra‐hepatic manifestations of hepatitis E virus. Methods Retrospective review of data of 106 cases of autochthonous hepatitis E (acute n = 105, chronic n = 1). Results Eight (7.5%) cases presented with neurological syndromes, which included brachial neuritis, Guillain‐Barré syndrome, peripheral neuropathy, neuromyopathy and vestibular neuritis. Patients with neurological syndromes were younger (median age 40 years, range 34–92 years, P = 0.048) and had a more modest transaminitis (median ALT 471 IU/L, P = 0.015) compared to cases without neurological symptoms [median age 64 years (range 18–88 years), median ALT 1135 IU/L]. One patient presented with a cardiac arrhythmia, twelve patients (11.3%) presented with thrombocytopenia, fourteen (13.2%) with lymphocytosis and eight (7.5%) with a lymphopenia, none of which had any clinical consequence. Serum electrophoresis was performed in 65 patients at presentation, of whom 17 (26%) had a monoclonal gammopathy of uncertain significance. Two cases developed haematological malignancies, acute myeloid leukaemia and duodenal plasmacytoma, 18 and 36 months after presenting with acute hepatitis E infection. Conclusions A range of extra‐hepatic manifestations can occur with hepatitis E. Neurological and haematological features of hepatitis E infection are relatively frequent in this UK cohort, and result in significant morbidity which warrants further study.